Application of molecular marker-assisted selection in breeding for improved farmer/market preferred cassava varieties in Tanzania - Kullaya, A.; Mkamilo, G.S.; Mtunda, K.; Kulembeka, H.P.; Masumba, E.; Marandu, E.; Kanju, E.; Ferguson, Morag E.; Ospina, C.; Marin, E.J.; Santos, Luís Guillermo; Barrera, E.; et al. (International Institute of Tropical Agriculture, 2010)
Tanzania is the fifth largest producer of cassava in Africa, the eighth largest producer in the world with an estimated average yields of about 10.4 t/ha, which is far below the potential yield of the crop. The low yield is caused by a number of factors including susceptibility of commonly grown varieties to major diseases and pests including susceptibility of local varieties to major diseases and pests such as cassava mosaic diseases (CMD), caused principally by East African Cassava Mosaic Virus (EACMV), its Ugandan variant (UgV), and African Cassava Mosaic virus (ACMV), Cassava Brown Streak Disease (CBSD), Cassava Bacterial Blight (CBB), Cassava Green Mite (CGM) and Cassava Mealy Bug (CMB). A project entitled, ‘Molecular Marker-Assisted Selection (MAS) and Farmer Participatory Improvement of Cassava Germplasm for Farmer/Market Preferred Traits in Tanzania’ was initiated to speed up the process of improving local cassava germplasm for resistance to pests and diseases in Tanzania. Improved genotypes with resistance to CMD, CGM, and CBB were introduced to Tanzania in 2003 from the International Centre for Tropical Agriculture (CIAT) Colombia and crossed with susceptible, farmer preferred varieties from the Eastern and Southern zone of Tanzania. A total of 26,590 F1 genotypes were obtained, of which 13,320.were from controlled crosses and the remaining from open pollination. The F1 genotypes were phenotypically evaluated for CMD resistance under high disease pressure at Chambezi Experimental Station in Tanzania; and at 6 six months after planting (MAP) 18,017 plants were surviving in the field, of which 11,606 were from controlled pollination and 6,411 from open pollination. About one third of the plants (6,000) did not show any CMD, CGM and CBSD symptoms. These were then subjected to marker assisted selection using four molecular markers associated with resistance to CMD, namely RME1, RME4, NS158 and NS169. The MAS results revealed that the percentage of individuals having marker alleles associated with CMD2 for 2 markers ranged between 69.8 and 89.5% in the controlled crosses and 69.1 and 83.8 in the open pollinated crosses. The results showed that 80% of all individuals selected as resistant using phenotypic evaluation were found to be resistant by MAS. This suggests that broad sense heritability for CMD resistance at the Chambezi Station during the first year evaluation was about 0.8. Although Chambezi is a very high CMD intensity site, MAS could still increase selection efficiency for CMD resistance by 20%.